2020
DOI: 10.20473/ijph.v15i1.2020.122-132
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Food Choice in Obesity

Abstract: The prevalence of obesity is increasing at all ages in Indonesia. Obesity does not only cause health complications, such as dyslipidemia, cardiovascular disease, cancer, and osteoarthritis but also has a negative effect on a countr’s socioeconomic conditions. Previous studies have explained that food choices affect the incidence of obesity. This literature review aims to explain the factors that influence the food choice related to obesity. Genetic and environmental factors affect the food choice in individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…However, it has also been found that obese women rarely consume vegetables and fruits, and prefer only particular types of vegetables and fruits. This is consistent with a study by Widjaja (2020) and Prihaningtyas (2020) on teenagers, which found obese teenagers to consume less fruits and more fried foods [40,41].…”
Section: Currentsupporting
confidence: 93%
“…However, it has also been found that obese women rarely consume vegetables and fruits, and prefer only particular types of vegetables and fruits. This is consistent with a study by Widjaja (2020) and Prihaningtyas (2020) on teenagers, which found obese teenagers to consume less fruits and more fried foods [40,41].…”
Section: Currentsupporting
confidence: 93%
“…Its complex figures are depicted in Figure 8. β-Amyrone 612782 −16.1 (1) Clofibrate 2796 −6.4 (2) Gemfibrozil 3463 −6.3 (3) Ciprofibrate 2763 −5.4 (4) Bezafibrate 39042 −5.8 (5) Fenofibrate 3339 −5.4 β-Stigmasterol 6432745 −10.8 (6) Cardarine 9803963 −8.5 β-Amyrone 612782 −14.0 (7) Pioglitazone 4829 −7.7 (8) Rosiglitazone 77999 −7.4 (9) Lobeglitazone 9826451 −7.3 β-Amyrone 612782 −21.5 β-Amyrone 612782 −13.2 β-Amyrone 612782 −15.4 (10) GW3965 447905 −11.9 (11) T0901317 447912 −8.2 Neotocopherol 86052 −7.5 (12) AT13148 24905401 −6.9 (13) Afuresertib 46843057 −6.9 (14) Alliin 87310 −4.8 Xanthosine 64959 −7.4 (15) APX-115 free base 51036475 −7.2 (16) Resatorvid 11703255 −7.1 (17) Myrislignan 21636106 −7.1 (18) Muscone 10947 −6.7 (19) 2 ,5 -Dihydroxyacetophenone 10279 −6.5 (20) α-Cyperone −6.3 (21) Veratric acid 7121 −6.1 (22) Triolein −5.5 (23) Methylthiouracil 667493 −5.4 (24) Falcarindiol −5.2 Ethyl palmitate 12366 −6.4 (25) BAW2881 16004702 −7.6 Ethyl palmitate 12366 −6.4 (26) Midostaurin −11.0 Sitostenone −8.5 (27) Suramin 5361 −15.4 β-Amyrone 612782 −14.4 (28)…”
Section: The Construction Of a Signaling Pathway-target Protein-bioactive (Stb) Networkmentioning
confidence: 99%
“…Clinically, the criteria of obesity is the that Body Mass Index (BMI) is equal to 30.0 or higher [5]. Obesity can present at all ages, globally, a report announced that the number of overweight and obese individuals will be projected to be 1.35 billion and 573 million by 2030 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, selecting healthy food choices and controlling food portion can increase life expectancy and reduce the risk of health problems among adults (Fadnes et al, 2022;Schulze et al, 2018;Yip et al, 2019). However, choosing and determining food portion can be complex due to various personal and social factors (Carruba et al, 2023;Widjaja & Prihaningtyas, 2020).…”
Section: Introductionmentioning
confidence: 99%